2007
DOI: 10.1007/s11746-007-1094-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Attapulgite Pore Size Distribution on Soybean Oil Bleaching

Abstract: The pore size distribution and specific surface area of the attapulgite is a crucial parameter for the uptake of pigments of oil. Bleaching of the soybean oil with three attapulgites with different pore size distribution, which were assigned a, b, and c, respectively was investigated. The specific surface area and the pore size distribution of the attapulgites were characterized. The Freundlich isotherm analysis was used to evaluate the sorption capacity of the three attapulgite. Sample b gave the highest surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 25 publications
4
17
0
1
Order By: Relevance
“…The results obtained in the current study were consistent with findings of Chalvatzi et al [11] in which laying hens given diets supplemented with 1.0 % palygorskite for 24 weeks produced eggs with significantly lighter eggshell and yolk color. Most of the variation in meat color of normal meat quality can be explained by the pigment content, myoglobin forms, and internal reflectance [6], which in turn suggested that the reduced meat color (yellowness and redness) observed in this study may be due to the affinity between palygorskite and pigments [13,41].…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…The results obtained in the current study were consistent with findings of Chalvatzi et al [11] in which laying hens given diets supplemented with 1.0 % palygorskite for 24 weeks produced eggs with significantly lighter eggshell and yolk color. Most of the variation in meat color of normal meat quality can be explained by the pigment content, myoglobin forms, and internal reflectance [6], which in turn suggested that the reduced meat color (yellowness and redness) observed in this study may be due to the affinity between palygorskite and pigments [13,41].…”
Section: Discussionmentioning
confidence: 58%
“…Activated clays including palygorskite, sepiolite, and bentonite are the popular adsorbents for decolorization of edible oil due to their less expensive price than activated carbon and high specific area and adsorption capacity [13,[38][39][40][41]. In poultry, Blair et al [9] noted that laying hens fed diets supplemented with spent bleaching clay, a bentonite product from canola oil refining, had reduced yolk color.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the adsorption amount of ␤-carotene was clearly high as compared with that of chlorophyll under the same adsorption conditions. This may be attributed to the smaller molecular size and chain structure conformation, ␤-carotene molecules, with little space resistance, are easier to adsorb on the surface of AAB or diffuse into the pores of AAB, because their molecular size is 2.1 nm × 0.8 nm × 0.7 nm as compared to the larger molecular size of chlorophyll (3.0 nm × 1.7 nm × 1.3 nm) and net structure of chlorophyll [25].…”
Section: Adsorption Kineticsmentioning
confidence: 99%
“…Another promising material for these systems is clay or a clay-based matrix, which is chemically inert, resistant to deterioration, commercially available in large quantities and has many industrial, catalytic and environmental applications [19][20][21][22][23][24][25] or fibrous morphology, is characterized by a porous crystalline structure containing tetrahedral layers alloyed together along longitudinal sideline chains [26]. Due to its unique structure and considerable textual properties, natural ATT has been widely used as adsorbents, adhesives, catalysts and as catalyst supports [27][28][29][30][31][32][33]. Zhao [29,32] prepared silver and copper modified ATT/TiO 2 photocatalysts by a hydrolysis method, which exhibited much higher activity than that of the pure TiO 2 for the degradation of methylene blue.…”
Section: Introductionmentioning
confidence: 99%